Improved High-Temperature Performance and Surface Chemistry of Graphite/LiMn2O4 Li-Ion Cells by Fluorosilane-Based Electrolyte Additive. (1st April 2015) - Yamagiwa, Kiyofumi; Morita, Daichi; Yabuuchi, Naoaki; Tanaka, Tatsuya; Fukunishi, Mika; Taki, Takayuki; Watanabe, Hiroaki; Otsuka, Takahiro; Yano, Toru; Son, Jin-Young; Cui, Yi-Tao; Oji, Hiroshi; et al.
Graphical abstract: Abstract: For graphite/LiMn2 O4 based lithium-ion batteries, we have successfully improved the charge/discharge capacity retention during high temperature cycling at 60 °C by addition of proper amount of 1, 2-bis(difluoromethylsilyl) ethane (FSE) into the electrolyte as an additive. In addition, the additive also suppresses self-discharge in a storage test at 60 °C for 7 days. Detailed surface analyses of graphite negative electrodes by electron microscopy, synchrotron X-ray photoelectron spectroscopy, and time of flight secondary ion spectroscopy, indicate that silicon and fluorine-containing thin layer is formed by FSE decomposition and deposited on the graphite negative electrode surface, which effectively protects the graphite negative electrode during the high temperature cycling and storage. The silicon- and fluorine-containing surface layer suppresses the degradation of the negative electrode caused by deposition of manganese, resulting from Mn 2+ dissolution from LiMn2 O4, and prevents self-discharge due to excess decomposition of electrolyte on the surface.